Newton and the Netherlands : How Isaac Newton was Fashioned in the Dutch Republic - Maas, Ad, 1970-; Jorink, Eric (Book collections on Project MUSE., 2012)
In the course of the eighteenth century, Newton's ideas (in different guises and interpretations) became a veritable hype in Dutch society. In Newton & the Netherlands Newton's sudden success is analyzed in great depth and put into a new perspective.